El juego y la motricidad gruesa en los niños de 4 a 5 años de la unidad educativa Manuel Ignacio monteros Valdivieso ubicada en la ciudad de Loja, en el período 2019 - 2020 - Leiva Delgado, Janina Alexandra (2021)
To play is an innate activity that in addition produce fun, happiness, amusement in children its result essential to develop motor, intellectual and social aspects, whence it is important to provide activities that require movement in order to stimulate the correct development of motor skills; for that reason is that the present research work has as a general objective: to analyze the importance of games in gross motor skills in children from 4 to 5 years, basing in a non-experimental research design, with a mixed type research approach, for this was taken into a sample of 23 children and 1 teacher, the methods used were: descriptive, analytical-synthetic, inductive-deductive which served to collect the data, as a technique was applied a direct interview to the teacher to know the strategies used in the teaching-learning process with children from 4 to 5 years, and as an instrument was used the Abbreviated Development Scale (EAD-1) of Nelson Ortiz allowing to diagnose that 4% of children investigated are located at the alert level and 96% at the medium level, presenting problems in the development of gross motor skills when performing activities such as: walking on tiptoe, three or more steps on one foot, bounce and catch the ball, jump to feet together rope 25cm and do wheelies alternating feet; therefore a guide of games was designed to strengthen gross motor skills in children, in order to achieve a correct motor development that allows them to development absolutely in their environment.